Transverse vibrations of circular annular plates with edges elastically restrained against rotation, used in acoustic underwater transducers - Vera Fernández, Sergio Andrés (2002)
Simply supported or clamped boundary conditions are rather ideal situations difficult to satisfy from a physical viewpoint. This paper considers a more "moderate" restriction: the case of edges elastically restrained against rotation for which no exact solution appears in the open literature. Eigenvalues corresponding to a wide range of the intervening geometric and mechanical parameters are determined. Good agreement is obtained with frequency coefficients determined two decades ago by means of a variational method. Obviously the problem is of basic interest in many ocean engineering applications: from the design of certain underwater acoustic transducers to pump and compressor elements passing through the design of naval vehicles and ocean structures. © 2002 Elsevier Science Ltd. All rights reserved.